Overview of control-flow hijacking attack and defense techniques for process - Fengfeng WANG; Tao ZHANG; Weiguang XU; Meng SUN (网络与信息安全学报)
Control flow hijacking attack is a common attack against computer software,which brings great harm to computer software security and is a research hotspot in the field of information security.Firstly,from the perspective of the source of attack code,the related research was expounded on process’s control flow hijacking attack.Secondly,according to the newest development status of control flow hijacking attack technology,the related defense technologies at home and abroad were introduced based on different defense ideas.Finally,the development trend of control flow hijacking offensive and defensive technology were summarized.